ISOTOPE ANALYSIS METHOD (δ13C) IN CLARIFIED APPLE JUICE - FIGUEIRA, RICARDO; CARLOS DUCATTI, CARLOS DUCATTI; MISCHAN, MARTHA MARIA; VENTURINI FILHO, WALDEMAR GASTONI (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
The aims of this study were to develop the method of isotope analysis to quantify the carbon of the C3 photosynthetic cycle in commercial clarifi ed apple juices and to measure the legal limit based on Brazilian legislation in order to identify the beverages that do not conform to the guidelines of the Ministry of Agriculture, Livestock and Food Supply (MAPA). This beverage was produced in a laboratory, according to Brazilian legislation. Adulterated juices with a sugarcane quantity above the legal limit were also produced. Isotope analyses measured the relative isotope enrichment of clarifi ed apple juices and their purifi ed sugar fraction. From these results the C3 source concentration was estimated by means of the isotope dilution equation. To determine the existence of adulteration in commercial juices it was necessary to create a legal limit according to Brazilian legislation. Two commercial brands of clarifi ed juice were analyzed. Taking the C3 source concentration and the ºBrix of commercial clarifi ed juices, together with the legal limit, it was possible to verify that one sample certainly contained more sugarcane than the quantity established by the MAPA. The development of a legal limit was an important methodological innovation that made it possible to identify the beverages that did not conform to Brazilian legislation. The methodology developed proved effi cient for quantifying the carbon of C3 origin in commercial clarifi ed apple juices.